1. The problem statement, all variables and given/known data (ds/dy)=(y+2s)/(y-2s) 2. Relevant equations 3. The attempt at a solution I let V= s/y and this gave me *(ds/dy)=(1+2V)/(1-2V) Then because V= s/y I said s=Vy and (ds/dy)=V + y(dV/dy) Right so then my equation looked like V + y(dV/dy)=(1+2V)/(1-2V) and then obviously I could do this : y(dV/dy)=(1+2V)/(1-2V) - V then because I wanted to make V part of the quotient so It becomes (1+V+2V^2)/(1-2V) = y(dV/dy) now this is a separable equation, so I can transform it to (dy/y)= (1-2V)(dV)/(1+V+2V^2) so, integrating both sides gives me LN|y|= the integral of the right side, but, how do you do this? this is where I get lost. I think the answer might be that (1+2V)/(1-2V) can be re written in a simplified way buit I cant remember it. Plz help.